2015
DOI: 10.3855/jidc.5871
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of coagulase-negative staphylococci isolated from bovine mastitis and detection of β-lactam resistance

Abstract: Introduction: Bovine mastitis is a frequent cause of economic loss in dairy herds. Coagulase-negative staphylococci (CoNS) are increasing in importance as cause of bovine intramammary infection throughout the world in recent years. CoNS have been isolated from milk samples collected from cows with clinical and subclinical mastitis in several countries. Identification of mastitis pathogens is important when selecting appropriate antimicrobial therapy. Methodology: A total of 93 strains of Staphylococcus spp iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…CoNS were earlier considered as the minor group of bacteria with less pathogenicity, as they were only reported in sub-clinical mastitis cases and hence, less attention was paid toward them (Pyörälä and Taponen, 2009). However, reports of clinical mastitis infection caused by various CoNS species have now surfaced largely and they have emerged as an important pathogen (Pyörälä and Taponen, 2009; Preethirani et al, 2015; Srednik et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CoNS were earlier considered as the minor group of bacteria with less pathogenicity, as they were only reported in sub-clinical mastitis cases and hence, less attention was paid toward them (Pyörälä and Taponen, 2009). However, reports of clinical mastitis infection caused by various CoNS species have now surfaced largely and they have emerged as an important pathogen (Pyörälä and Taponen, 2009; Preethirani et al, 2015; Srednik et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…However, methicillin resistant Staphylococcus aureus (MRSA) have been more widely studied and well characterized in comparison to MRS especially in India (Monecke et al, 2007; Fessler et al, 2010; Türkyilmaz et al, 2010). Increased drug exposure and use of antibiotics in animal diseases also poses a hazard to human health whose impact and effect is still not well characterized but may result in emergence of antibiotic resistant strains making the surveillance of antibiotic susceptibility very crucial (Pyörälä and Taponen, 2009; Fessler et al, 2010; Preethirani et al, 2015; Srednik et al, 2015). Another, concern associated with CoNS is that they may also act as reservoirs of antimicrobial resistance genes (Becker et al, 2014), and can transfer the resistance gene into the S. aureus genome leading to the development of new and multidrug resistant strains (Otto, 2012; Vitali et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth highlighting that the low sensitivity of the phenotypic methods used in the present study may be due to the non-expression of the blaZ gene, as pointed out by Srednik et al (2015).…”
Section: Resultsmentioning
confidence: 89%
“…It was observed that the most penicillin-resistant isolates harbored the blaZ gene and produced β-lactamase, suggesting that the enzymatic inactivation of β-lactam antimicrobials is the most predominant resistance mechanism expressed by the assessed CoNS. As shown in previous studies, staphylococci are key reservoirs of β-lactam resistance markers, which are normally present in mobile DNA, such as conjugative plasmids and transposons, contributing to the transferability of these antimicrobial resistance genes between different species or genera, which is extremely important to human and veterinary medicine (Srednik et al, 2015;Haubert et al, 2017;Nobrega et al, 2018).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation